Aerobic and anoxic utilization of organic matter for flexible nitrite supply in nutrient conversion pathways based on anaerobic ammonium oxidation: Microbial interactive mechanism - Yun, Wonsang; Cho, Kyungjin; Jung, Jinyoung; Choi, Daehee (Elsevier BV, 2024)
This study investigated nutrient conversion pathways and corresponding interactive mechanisms in a mainstream partial-nitritation (PN)/anaerobic ammonium oxidation (anammox)/partial-denitrification-(PD)enhanced biological phosphorus-removal (EBPR) (PN/A/PD-EBPR) process. A laboratory-scale sequencing batch reactor was operated for 301 days under different operational strategies. Mainstream PN/A/PD-EBPR was successfully operated with aerobic and anoxic utilization of organic matter. Aerobic utilization of organic matter was an effective strategy for conversion to denitrifying polyphosphate-accumulating organism-based phosphorus removal, referring to a biological reaction that outperformed nitrite-oxidizing bacteria. Aerobically adsorbed organic matter could be used as a carbon source for PD, which further enhanced nitrogen removal by PN/A. Ultimately, the interaction between complex nutrient conversion pathways served to achieve stable performance. High-throughput sequencing results elucidated the core microbe functioning in the mainstream PN/A/PD-EBPR process with respect to various nutrients. The outcomes of this study will be beneficial to those attempting to implement mainstream PN/A/PD-EBPR.